Duty to obey the lawful and reasonable orders of the employer: with reference to Ngeow Voon Yean v. Sungai Wang Plaza Sdn Bhd / Landmarks Holdings Bhd - Ali Mohamed, Ashgar Ali (The Malaysian Current Law Journal Sdn Bhd, 2010)
The employer and employee relationship is viewed as 'a close personal relationship' and as such there must be complete confidence and trust between the parties to the employment contract. The employer is to act fairly and reasonably when dealing with their employees. Likewise, an employee must render the services to the employer faithfully and loyally. One of the fundamental duties of an employee at common law is to obey all the lawful and reasonable orders and instructions of the employer. Failure to carry out the lawful and legitimate instructions of the superior would constitute a material or fundamental breach of the contract or a major misconduct. The emphasis here is that the superior order must be lawful and reasonable. It cannot be unlawful or an unreasonable act. It follows that if the superior order is manifestly illegal or dangerous, the employee can refuse to obey the order. Having said the above, this article will discuss inter alia, the duty to obey all the lawful and reasonable orders of the employer with special reference to the Federal Court's decision in Ngeow Voon Yean v. Sungei Wang Plaza Sdn Bhd / Landmarks Holdings Bhd.